In the margins : [large type] on the pleasures of reading and writing - Ferrante, Elena (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"Here, in these four crisp essays on writing and reading by the internationally bestselling author of My Brilliant Friend and The Lying Life of Adults, Ferrante offers a rare look at the origins of her literary powers. She writes about her influences, her struggles, and her formation as both a reader and a writer; she describes the perils of "bad language" and suggests ways in which it has long excluded women's truth; she proposes a choral fusion of feminine talent as she brilliantly discourses on the work of Emily Dickinson, Gertrude Stein, Ingeborg Bachmann, and many others" --